Bureacrats and Colonos: State Formation in Southeastern Colombia - Sandra Patricia Martínez Basallo (Íconos)
From an anthropological approach to the study of the state, the article discusses the process of local state formation in southeastern Colombia from the analysis of the interactions arising between officials and beneficiaries of agricultural policies implemented in this region between 1960 and 1980. The examination of this phenomenon shows the continuous transfer the boundaries between state and non-state actors who, involved in a complex process of negotiation of domination interact in an unstable field of relations that fluctuate between proximity and distance that unites them or separates them.